Pendekatan Akhlak dan Filsafat Esensialisme dalam Pendidikan Islam untuk Mengatasi Dekadensi Moral Peserta Didik - Mochamad Daffa Akmal; Daffa Tantra Pratama; Alif Rabbani Yusuf; Bella Dwi Pertiwi (CV. ITTC INDONESIA, 2025)
This study aims to analyze the integration of moral values (akhlaq) and the philosophy of essentialism in Islamic education as an effort to address students’ moral problems in the era of globalization. The moral crisis—such as bullying, lack of empathy, and social deviance—reflects the weak internalization of spiritual values within the educational system. Using a Systematic Literature Review (SLR) approach, this research identifies, evaluates, and synthesizes relevant studies published between 2017 and 2025. Out of 25 reviewed articles, five were selected as the primary sources. The findings reveal that (1) character development through teacher role modeling, habituation of religious practices, and parent–school collaboration is effective in preventing juvenile delinquency; (2) essentialist philosophy aligns with Islamic education by emphasizing the preservation of core values such as faith, honesty, discipline, and responsibility; (3) the integration of moral values and essentialist principles in Islamic Religious Education as well as Qur’an memorization (tahfidz) programs significantly strengthens students’ character formation. Thus, Islamic education based on akhlaq and essentialism serves not only as a conceptual framework but also as a practical solution to nurturing a religious, ethical, and resilient young generation capable of facing contemporary challenges.